The lesion of kidney glomeruli in case of polyomavirus allograft nephropathy - Yu. G. Motin; O. V. Omelchenko; D. B. Lokchin; S. V. Gappoev; E. N. Semenova; A. Yu. Prokchozhev; V. A. Yakovlev; E. V. Grigorov; A. Yu. Gryzlov; A. L. Klyuev (Вестник трансплантологии и искусственных органов)
The article describes a case of diagnosis allograft polyomavirus nephropathy with glomerular involvement. Immunohistochemical and electron microscopic methods were used to exam the transplant kidney biopsies, which showed morphological changes in allograft, ultrastructural characteristics of polyomavirus and features of its spread in kidney tissue structures.